posted by .

How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?
A. shift the graph 3 units right
b. shift the graph 3 units up
c. shift the graph 3 units down
d. shift the graph 3 units left

the graph was shifted up 3 from the original graph that's all the question wants to know

Ladybug, you often tend to forget to put in brackets, so
if you shift
y = 3√x
" to the left 3 units" (d)
you get y = 3√(x+3)

whereas y = 3√x + 3 would have been "up 3 units" (b)

## Similar Questions

1. ### calculus

Given the graph of f(x) find the graph of 2 f( -3x - 2) - 4 Is this correct?
2. ### calculus reposted

Given the graph of f(x) find the graph of 2 f( -3x - 2) - 4 Is this correct?

How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?

How can the graph of g(x)=3square root x+3 be obtained from the graph of g(x)= 3 square root x?

the graph of y=1/3 3square root x+5 can be obtained from the graph of y=3square root x by which transformations?